A prospective study of the hypertriglyceridemic waist phenotype and risk of incident ischemic stroke in a Chinese rural population. (25th March 2018) - Wang, W.; Shen, C.; Zhao, H.; Tang, W.; Yang, S.; Li, J.; Ren, Z.; Zhao, Y.
Abstract : Objectives: The hypertriglyceridemic waist phenotype has been reported as a practical tool to screen people with an increased risk of coronary artery disease and type 2 diabetes. The aim of this study was to investigate the relationship between the phenotype and ischemic stroke in a rural population in south China. Materials and methods: A total of 4081 participants aged over 35 years old without a stroke history were surveyed in 2009 and followed up from May 2014 to January 2016. The hypertriglyceridemic waist phenotype was defined as a waist circumference ≥90 cm and a triglyceride level ≥2.0 mmol/L in males, and a waist circumference ≥85 cm and a triglyceride level ≥1.5 mmol/L in females. A Cox regression model was used to estimate the association of the phenotype and ischemic stroke. Results: After a mean of 5.16 years of follow‐up, 138 individuals developed ischemic stroke. The hypertriglyceridemic waist phenotype was significantly associated with an increased risk of ischemic stroke before and after adjustment for confounding factors; the hazard ratios and 95% confidence intervals were 1.94 (1.27‐2.96) and 1.71 (1.05‐2.78), respectively. Further stratified analysis confirmed the associations in females (2.37 [1.09‐5.14]) and smokers (3.20 [1.30‐7.92]). A significant association of the phenotype and ischemic stroke risk was observed in subjects with normal glucose levels (2.94 [1.58‐5.47]) but not in subjects with impaired fasting glucose and diabetes. Conclusions: The hypertriglyceridemic waist phenotype is associated with an increased risk of ischemic stroke and might be a simple tool to screen individuals with a high risk for ischemic stroke.